Buyer Guarantees at the Stage of Concluding a Contract for the Sale of Real Estate under Construction - Daher, Zainab Abd ALameer; Hussein, Raad Aday (Journal of Ecohumanism, 2024)
If the contract for the sale of real estate under construction was intended to economically address the need of individuals for housing, the aforementioned contract failed to achieve the desired goal as a result of the emergence of many real estate investors who tried to exploit the need of individuals for housing in light of this housing crisis. We often hear about the failure to complete many residential complexes or the sale of the residential unit to more than one buyer or the seller escaping with the money of the bookers, so the buyers find themselves without effective protection. Therefore, the above risks have highlighted the need to include many guarantees that ensure the protection of the buyer in the contract for the sale of real estate under construction, thus ensuring that those who purchase residential units under construction are protected from exploitation and greed of investors. It is worth noting thatThe contract for the sale of real estate under construction stipulates a set of guarantees that ensure the buyer that the seller will fulfill his contractual obligations. The buyer in the contract for the sale of real estate under construction is exposed to the risk of the seller not completing the project. This risk does not exist in the normal sale, as it applies to a property that exists at the time of contracting. Therefore, we find that the laws regulating this contract have stipulated a set of guarantees that aim to provide adequate protection for the buyer, and that some of these guarantees do not go beyond the guarantees stipulated in the normal contract for sale, and someHaOther are new guarantees specific to the contract of sale of real estate under construction.